Strategi Pembelajaran Berbasis Masalah (Problem-Based Learning) dalam Meningkatkan Kemampuan Berpikir Kritis Peserta Didik - Yeni Nuraeni; Ulffa Tuzzami; M Akbar Pratama; Anita Anggraeni (Jurnal Bersama Ilmu Pendidikan (DIDIK), 2025)
This study aims to describe the application of Problem-Based Learning (PBL) strategies to improve students' critical thinking skills. The research method used was a literature review analyzing various relevant sources. The results indicate that PBL can facilitate students in identifying problems, analyzing information, formulating solutions, and logically evaluating their thinking. Therefore, PBL can be used as an effective learning strategy in developing students' critical thinking skills at various levels of education.PBL is a learning approach that uses real-world problems as a context for students to learn critical thinking, solve problems, and acquire essential knowledge and concepts from the subject matter. This model was first developed in 1969 at McMaster University School of Medicine, Canada, to address health issues and was later adapted for general education to improve student learning outcomes. Through PBL, students are encouraged to learn independently, seek relevant information, and collaborate with peers to identify and solve learning problems. This approach trains students in analysis, creativity, and independence, while also increasing motivation for discussion and the contribution of ideas. Thus, PBL is significantly more effective than conventional learning in training students to think critically and solve problems.